Knowledge is a river and education is like a stairway: An eye movement study on how L2 speakers process metaphors and similes - Olkoniemi Henri; Bertram Raymond; Kaakinen Johanna K. (Cambridge University Press, 2022)
Very little is known about the processes underlying second language (L2) speakers’ understanding of written metaphors and similes. Moreover, most of the theories on figurative language comprehension do not consider reader-related factors. In the study, we used eye-tracking to examine how native Finnish speakers (N = 63) read written English nominal metaphors (“education is a stairway”) and similes (“education is like a stairway”). Identical topic–vehicle pairs were used in both conditions. After reading, participants evaluated familiarity of each pair. English proficiency was measured using the Bilingual-language Profile Questionnaire and the Lexical Test for Advanced Learners of English. The results showed that readers were more likely to regress within metaphors than within similes, indicating that processing metaphors requires more processing effort than processing similes. The familiarity of a metaphor and L2 English proficiency modulated this effect. The results are discussed in the light of current theories on figurative language processing.